Faktor-Faktor Yang Mempengaruhi Firm Financial Performance - Monica, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2019)
The objective of this research is to obtain empirical evidence on the influence of firm size ratio, firm age, the ratio of asset turn over, the ratio of asset tangibility, and CEO-Duality toward firm financial performance. The study uses data from manufacturing companies listed on Indonesian Stock Exchange during 2015-2017. The results of this study indicates the ratio of asset turn over, the ratio of firm size and firm age that have a significant influence on firm financial performance, while the ratio of asset tangibility and CEO-Duality has no effect on firm financial performance. To further complement future research, increase the number of samples, by using companies that does not only cover the manufacturing sector, also extends the research period and uses additional variables that can affect the company’s financial performance